1991
DOI: 10.1007/bf00310134
|View full text |Cite
|
Sign up to set email alerts
|

Fine-structural localization of aldose reductase and ouabain-sensitive, K+-dependent p-nitro-phenylphosphatase in rat peripheral nerve

Abstract: Aldose reductase was visualized by light and electron microscopy using a goat anti-rat antibody with immunoperoxidase and immunogold, respectively. Ouabain-sensitive, K(+)-dependent, p-nitro-phenylphosphatase, a component of (Na+, K+)-ATPase, was localized at the electron microscopic level by enzyme histochemistry using p-nitro-phenylphosphate as substrate. In peripheral nerve, spinal ganglia and roots, the Schwann cell of myelinated fibers was the principal site of aldose reductase localization. Immunostainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…However, we did not detect dynorphin A in axons of diabetic rats and the cellular distribution remained restricted to non-neuronal cells. Schwann cells are the primary lesion site for many hyperglycaemia-induced nerve changes, as they contain aldose reductase [26] and it is plausible that increased dynorphin A production represents another intracellular response to increased flux through the polyol pathway, although we have yet to investigate this possibility. When considering the functional consequences of increased dynorphin A in peripheral nerve during diabetes, it is noteworthy that the increase was coincident with the presence of tactile allodynia and formalin-evoked hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not detect dynorphin A in axons of diabetic rats and the cellular distribution remained restricted to non-neuronal cells. Schwann cells are the primary lesion site for many hyperglycaemia-induced nerve changes, as they contain aldose reductase [26] and it is plausible that increased dynorphin A production represents another intracellular response to increased flux through the polyol pathway, although we have yet to investigate this possibility. When considering the functional consequences of increased dynorphin A in peripheral nerve during diabetes, it is noteworthy that the increase was coincident with the presence of tactile allodynia and formalin-evoked hyperalgesia.…”
Section: Discussionmentioning
confidence: 99%
“…4). This is striking because of the inhibition of JNK phosphorylation by fidarestat, an inhibitor of an enzyme thought to be primarily in the Schwann cell and not the axon [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in which expression of enzymes involved in the polyol pathway has been manipulated have placed a particular focus on the metabolic consequences of excessive metabolism of glucose to sorbitol owing to high activity of aldose reductase [35][36][37][38] . On the basis of the involvement of the polyol pathway, the perception of diabetic neuropathy as a micro vascular complication of diabetes has been underpinned by immunocytochemical studies that showed localization of aldose reductase to the endothelial cells of epineurial and dorsal root ganglion blood vessels and to perivascular sympathetic axons [39][40][41] . Indeed, recent data implicates aldose reductase activity in the production of endothelial proinflammatory and prothrombotic signals 42 , a pathogenic cascade that is currently receiving close attention in the context of diabetic neuro pathy 42 and is discussed in detail below (see the section 'Microvascular changes in Schwann cells').…”
Section: Schwann Cells In Diabetic Neuropathymentioning
confidence: 99%
“…Indeed, recent data implicates aldose reductase activity in the production of endothelial proinflammatory and prothrombotic signals 42 , a pathogenic cascade that is currently receiving close attention in the context of diabetic neuro pathy 42 and is discussed in detail below (see the section 'Microvascular changes in Schwann cells'). However, within the endoneurium, aldose reductase is restricted to the myelinating Schwann cells of somatic nerves and to satellite glial cells in the dorsal root ganglia [39][40][41] …”
Section: Schwann Cells In Diabetic Neuropathymentioning
confidence: 99%